A sweet emergency due to bitter poisoning—A case report - Jenny Joseph; Saravanan Thangavelu; J Shanjitha; Deepak Jacob (Journal of Family Medicine and Primary Care)
Organophosphorus compounds (OPC) are major components of pesticides and nerve gas agents. Self-harm by ingestion of OPC pesticides is one of the common problems encountered in the emergency room (ER), especially in developing countries such as India. It is recognised by the World Health Organization (WHO) as the third most prevalent means of suicide. In addition to the cholinergic effects caused by these agents, they can induce metabolic dysregulations. We present a case of a 22-year-old male patient, without previous history of diabetes, who was brought to the ER in an unresponsive state with an HbA1c of 5%. His initial laboratory investigations revealed hyperglycemia, high anion gap metabolic acidosis, ketonuria, and glycosuria. His relatives revealed intentional ingestion of OPC. He was treated for both OPC poisoning and hyperglycemic ketoacidosis. Adequate acute care was instigated though prognosis could not be gauged due to the early discharge of the patient against medical advice. This case highlights that OPC poisoning can be a possible etiological factor for hyperglycemic ketoacidosis. It can mimic diabetic ketoacidosis leading to delayed diagnosis. Thus, early identification and immediate management are crucial because of the effect of hyperglycemic ketoacidosis on the outcome of a patient with OPC poisoning.